Representasi Kunjungan Museum Monumen Perjuangan Rakyat Jawa Barat dalam Meningkatkan Nilai Nasionalisme Mahasiswa Institut Pendidikan Indonesia - Ardiana, Kadika Sira; Alfaro, Moch Kevin; Anggara, Permana; Insan, Sidik Jamaludin; Kurniati, Pat (CV. Kurnia Grup, 2024)
The West Java People's Struggle Monument is one of the important historical places in Bandung that has a strategic role in transforming collective memory and educating the younger generation about national values. This study aims to explore the representation of the museum visit program in increasing the value of nationalism of students of the Indonesian Institute of Education. This study uses qualitative research methods, this study collects data through in-depth interviews with museum guides, direct observation in museums can internalize nationalist values in students. The results of the study show that the West Java People's Struggle Monument Museum has a deep significance in awakening the value of nationalism. Through historical documentation, artifacts, and stories of struggle, the museum has succeeded in presenting a concrete representation of the nation's struggle, especially the values of unity, unity and unlimited sacrifice. A visit to the museum.